2008
DOI: 10.1136/jmg.2007.056416
|View full text |Cite
|
Sign up to set email alerts
|

Identifying pathogenic genetic background of simplex or multiplex retinitis pigmentosa patients: a large scale mutation screening study

Abstract: We elucidated the mutation spectrum in Japanese RP patients and demonstrated the validity of the mutation detection system using dHPLC sequencing for genetic diagnosis in RP patients independent of familial incidence, which may provide a model strategy for identifying genetic causes in other diseases linked to a wide range of genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 34 publications
(27 reference statements)
1
52
0
Order By: Relevance
“…Epidemiological studies assessing different populations have indicated that half of all mutations in patients with IRD are sporadic or multiplex, and, unfortunately, those cases are the ones most prevalent in the clinic. 19,29 In our cohort of patients with IRD, 90% of probands displayed sporadic or autosomal recessive mutations, which makes molecular diagnosis more challenging. 30 Several groups, including ours, have attempted to challenge the molecular diagnosis of simplex or autosomal recessive IRD 19,31,32 ; however, the detection rates remained lower than 20%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epidemiological studies assessing different populations have indicated that half of all mutations in patients with IRD are sporadic or multiplex, and, unfortunately, those cases are the ones most prevalent in the clinic. 19,29 In our cohort of patients with IRD, 90% of probands displayed sporadic or autosomal recessive mutations, which makes molecular diagnosis more challenging. 30 Several groups, including ours, have attempted to challenge the molecular diagnosis of simplex or autosomal recessive IRD 19,31,32 ; however, the detection rates remained lower than 20%.…”
Section: Discussionmentioning
confidence: 99%
“…19,29 In our cohort of patients with IRD, 90% of probands displayed sporadic or autosomal recessive mutations, which makes molecular diagnosis more challenging. 30 Several groups, including ours, have attempted to challenge the molecular diagnosis of simplex or autosomal recessive IRD 19,31,32 ; however, the detection rates remained lower than 20%. In this study, however, our results showed that 50% of patients with sporadic and 71% of patients with recessive IRD were successfully determined to have genetic predispositions, suggesting that targeted exome sequencing is an efficient and applicable approach for the molecular diagnosis of such patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…for 30 disease genes identified commonly within North American or European patients revealed candidate pathogenic mutations in only 14% of the cohort (8).…”
mentioning
confidence: 99%